Exploration of the potential for pseudo-ductility in thin ply CFRP angle-ply laminates via an analytical method. (20th May 2015) - Fuller, J.D.; Wisnom, M.R.
Abstract: Thin ply laminates have shown much promise in recent times in terms of their exciting damage suppression characteristics. Utilisation of this damage suppression in carbon–epoxy angle-ply laminates has been shown experimentally to yield a highly non-linear stress–strain response. This paper presents an analytical modelling method that incorporates matrix plasticity and reorientation of the fibres into a classical laminate analysis for the prediction of the in-plane response of thin ply angle-ply laminates. It is shown that the method can successfully predict the non-linear behaviour of [ ± θ 5 ] s laminates with values of θ between 15° and 45°. The main characteristics of the stress–strain curve, such as the initial largely linear region, yield point and stiffening before final failure, are all well captured. The modelling has allowed straightforward identification of a particular fibre angle that exhibits strength in excess of 900 MPa, strain to failure of more than 3.5% and a promising pseudo-ductile strain of 1.2%.